Continuity and Change: Comparing the Securitization of Migration under the Obama and Trump Administrations - (:unkn) unknown (My University, 2020)
One of the most contested issues in the 2016 U.S. Presidential Election was immigration: in particular, irregular migration across the U.S. border with Mexico. This paper seeks to examine the extent to which the securitization of immigration is an “isolated phenomenon” endemic to the Trump Administration, as opposed to a reality of U.S. policymaking that has pervaded previous administrations. By contrasting the immigration platform of the current administration with that of its predecessor, led by Barack Obama, this paper will assert that, despite the intensification of rhetoric against irregular migrants, much of the Trump Administration’s response to immigration from the Southern border has been informed by, and is directly continuous with, actions taken by Obama between 2008 and 2016. It will argue that the same three factors: the post 9-11 conception of migration as an inherent threat, the deportation regime and the securitization (and sometimes militarization) of the southern border, have rendered the last decade of American immigration policy more or less consistent, despite vastly different stated ideological underpinnings.